'A Joycean Smutmonger': Echoes of Joyce in Máirtín Ó Cadhain's Rural Modernism - Niall Ó Cuileagáin (Review of Irish Studies in Europe, 2024)
Since its publication, critics of Máirtín Ó Cadhain’s Irish-language masterpiece Cré na Cille (1949; Graveyard Clay) have consistently namechecked James Joyce’s Ulysses (1922), usually for the sole purpose of conveying its perceived difficulty and/or vulgarity. Indeed, Cré na Cille was first refused publication because, in Ó Cadhain’s words, it was too long and too ‘Joycean’. Ó Cadhain himself evidently saw his work as existing in dialogue with his renowned progenitor and during a late lecture revelled in retelling an overheard conversation in which he was described as nothing more than a ‘Joycean smutmonger’. This article goes beyond such surface-level comparisons to unpick how Ó Cadhain proffers a radical portrayal of rural Irish modernity to compare with Joyce’s predominantly urban equivalent. It argues that Ó Cadhain’s characters, like those found in Joyce’s oeuvre, are consistently forced to navigate the forces of tradition and modernity, which existed at the heart of rural Irish society in the mid-twentieth century. This essay will first compare how Ó Cadhain and Joyce treat the predicaments of a young woman preparing for emigration in their respective short stories ‘An Bhliain 1912’ and ‘Eveline’, before moving on to treat Ó Cadhain’s experiments in form and language in Cré na Cille. In particular, it will examine such experimentation in the context of his lasting obsession with Finnegans Wake (1939), as evidenced by his stated belief that he ‘could write a work like Finnegans Wake’. Informed by recent developments in ‘alternative modernities’, this essay attempts to offer a nascent definition of what might be signified by ‘rural modernism’ in an Irish context.